2023
DOI: 10.3390/su151914296
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Innovation Performance through Big Data Analytics Powered by Artificial Intelligence Use: An Empirical Exploration of the Role of Strategic Agility and Market Turbulence

Omar. A. Alghamdi,
Gomaa Agag

Abstract: Scholars and practitioners have paid attention to the critical role of big data analytics driven by AI in enhancing business performance. However, firms investing in big data analytics often fail to achieve those advantages. Our research explores the critical role played by strategic agility and market turbulence on the link between big data analytics driven by AI and innovation performance. Based on dynamic capabilities view, we developed an integrated model to examine the relationship between our study varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…For example, in the pharmaceutical industry in Pakistan, Munir et al [45] found that a direct and positive link exists between BDACs and organizational IP. Similarly, Alghamdi and Agag [35] indicated in their study that big data analytics driven by AI from manufacturing companies has a significant and positive impact on IP. Similarly, through a survey of 421 Chinese managers and employees engaged in the field of big data analytics, Zhang and Yuan [29] found that BDACs have a positive effect on IP.…”
Section: Hypotheses Development 221 the Impacts Of Bdacs Sic And Oamb...mentioning
confidence: 90%
See 4 more Smart Citations
“…For example, in the pharmaceutical industry in Pakistan, Munir et al [45] found that a direct and positive link exists between BDACs and organizational IP. Similarly, Alghamdi and Agag [35] indicated in their study that big data analytics driven by AI from manufacturing companies has a significant and positive impact on IP. Similarly, through a survey of 421 Chinese managers and employees engaged in the field of big data analytics, Zhang and Yuan [29] found that BDACs have a positive effect on IP.…”
Section: Hypotheses Development 221 the Impacts Of Bdacs Sic And Oamb...mentioning
confidence: 90%
“…Consequently, it is complex to deal with traditional data-processing application software. Big data tools are emerging to help firms to collect, process, and analyze data to unlock valuable insights, solve business problems, increase agility and innovation, and make and drive better decisions [35]. Big data seeks to glean intelligence from data to create an opportunity and then translate it into business advantage [36,37].…”
Section: Big Data Analytics Capabilities (Bdacs)mentioning
confidence: 99%
See 3 more Smart Citations